2007
DOI: 10.1177/0009922806290455
|View full text |Cite
|
Sign up to set email alerts
|

Hemangiomas: An Overview

Abstract: Hemangiomas are the most common tumors of infancy 2 and are also the most common tumors of the head and neck in infancy. 3 The incidence of hemangiomas in the first 3 days of life is 1.1% to 2.6% 4,5 and increases to 8.7% to 12.7% between the ages of 1 month and 1 year of life. [6][7][8] Amir et al 8 found that the incidence of hemangiomas increased with prematurity. In infants with birth weights of less than 1500 grams, the incidence of hemangiomas was 15.6%, and as the birth weight decreased below 1000 grams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 129 publications
(185 reference statements)
2
30
0
Order By: Relevance
“…These results regarding CD105 immunostaining also suggest that, based on the assumption that this antibody is only expressed on newly formed vessels, tumor specimens [14]. Thus, in this series 50% of oral VMs were in the non-proliferative phase and 80% of OPGs were in the phase of development or endothelial proliferation, a fact emphasizing the importance of angiogenic mechanisms for the etiopathogenesis of these tumors [15].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These results regarding CD105 immunostaining also suggest that, based on the assumption that this antibody is only expressed on newly formed vessels, tumor specimens [14]. Thus, in this series 50% of oral VMs were in the non-proliferative phase and 80% of OPGs were in the phase of development or endothelial proliferation, a fact emphasizing the importance of angiogenic mechanisms for the etiopathogenesis of these tumors [15].…”
Section: Discussionsupporting
confidence: 63%
“…These results support the view that angiogenesis is an important process in the growth and development of different head and neck tumors. However, these findings do not emphasize only the similarity between oral VMs and PGs and the relevance of CD105 and CD34 immunostaining for the study of vascular neoformations, but also the tendency to consider that angiogenic factors play an important role in the pathogenesis of these tumors reported in several investigations [12,14,15]. However, the exact role of the angiogenesis and its relationship with the development of many tumors still needs to be clarified so that it can be used as a safe tool for the identification of the biological potential of the tumor and as a coadjuvant in available treatments.…”
Section: Discussionmentioning
confidence: 85%
“…Sclerotic therapy may be achieved by intralesional injections of corticosteroids, use of interferon, or by laser therapy, cryosurgery or radiations (22). Surgical excision and sclerotherapy are most commonly used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated a risk of pulmonary fibrosis in patients receiving more than 160 mg of bleomycin systemically (31). It is reported that the total dose must not exceed 5 mg/kg, or approximately 20 mg in total, for this to occur in infants (22).…”
Section: Discussionmentioning
confidence: 99%
“…Hemangioma is the most common vascular neoplasm of the head and neck and may be seen in various localizations (3,4). The ISSVA classification system divides hemangiomas into two types: infantile hemangiomas and congenital hemangiomas.…”
Section: Hemangiomamentioning
confidence: 99%